Evaluation of Alcoholic and Aqueous Extracts of Nicandra Physalodes Leaves for Diuretic Activity - Devi, P (International Journal of Pharmaceutical & Biological Archive, 2010)
Aqueous and alcoholic extracts of Nicandra physalodes leaves were tested for Diuretic activity in rats. The parameters studied on individual rat were body weight before and after test period, total urine volume, urine concentration of Na+, K+ and Cl -. In the present study alcoholic and aqueous extracts of Nicandra physalodes leaves (100mg/kg of body weight) showed increase in urine volume, cation and anion excretion. Furosemide was used as reference diuretic.